Erosive Wear Characteristics Analysis of High Chromium White Cast Iron using Finite Element Analysis (FEA) - Riki Hendra Purba; Deva Ihsan Khoirunas; James Julian; Fitri Wahyuni (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2025)
Erosive wear often occurs on heavy machinery operating under extreme conditions. This research utilizes the Finite Element Analysis (FEA) method with the Cowper-Symonds strain rate model to analyze the erosion behavior of high-Cr cast iron (HCCI) under different impact angles and compare it to other materials of different characteristics, such as 6061-T6 Aluminium, GH4720Li Superalloy, and Stainless Steel 304 Annealed. A single particle erosion model was made for this study. The erodent particle size used is 0.7 mm in diameter, with the target material measuring 1 x 1 x 0.5 mm. The particle velocity is kept constant at 25 m/s. Based on the simulation results, it can be known that HCCI performs the best at every impact angle. Moreover, from the model's cross-section, it's evident that the material's stress concentration aligns with the direction of movement of the erodent particle. Therefore, it can be concluded that these factors, along with others such as contact time, plastic strain, and surface deformation lead to variations in surface mechanics.